Transcription factor E93 specifies adult metamorphosis in hemimetabolous and holometabolous insects - Ureña, Enric (National Academy of Sciences, 2014)
All immature animals undergo remarkable morphological and physiological changes to become mature adults. In winged insects, metamorphic changes either are limited to a few tissues (hemimetaboly) or involve a complete reorganization of most tissues and organs (holometaboly). Despite the differences, the genetic switch between immature and adult forms in both types of insects relies on the disappearance of the antimetamorphic juvenile hormone (JH) and the transcription factors Krüppel-homolog 1 (Kr-h1) and Broad-Complex (BR-C) during the last juvenile instar. Here, we show that the transcription factor E93 is the key determinant that promotes adult metamorphosis in both hemimetabolous and holometabolous insects, thus acting as the universal adult specifier. In the hemimetabolous insect Blattella germanica, BgE93 is highly expressed in metamorphic tissues, and RNA interference (RNAi)-mediated knockdown of BgE93 in the nymphal stage prevented the nymphal–adult transition, inducing endless reiteration of nymphal development, even in the absence of JH. We also find that BgE93 down-regulated BgKr-h1 and BgBR-C expression during the last nymphal instar of B. germanica, a key step necessary for proper adult differentiation. This essential role of E93 is conserved in holometabolous insects as TcE93 RNAi in Tribolium castaneum prevented pupal–adult transition and produced a supernumerary second pupa. In this beetle, TcE93 also represses expression of TcKr-h1 and TcBR-C during the pupal stage. Similar results were obtained in the more derived holometabolous insect Drosophila melanogaster, suggesting that winged insects use the same regulatory mechanism to promote adult metamorphosis. This study provides an important insight into the understanding of the molecular basis of adult metamorphosis.